Communication Barriers and Infant Health: Intergenerational Effects of Randomly Allocating Refugees Across Language Regions - Daniel Auer; Johannes S. Kunz (Global Labor Organization (GLO), 2021)
This paper investigates the intergenerational effect of communication barriers on child health at birth using a natural experiment in Switzerland. We leverage the fact that refugees arriving in Switzerland originate from places that have large shares of French (or Italian) speakers for historical reasons and upon arrival are by law randomly allocated across states that are dominated by different languages but subject to the same jurisdiction. Our findings based on administrative records of all refugee arrivals and birth events between 2010 and 2017 show that children born to mothers who were exogenously allocated to an environment that matched their linguistic heritage are on average 72 gram heavier (or 2.2%) than those that were allocated to an unfamiliar language environment. The differences are driven by growth rather than gestation and manifest in a 2.9 percentage point difference in low birth weight incidence. We find substantial dose-response relationships in terms of language exposure in both, the origin country and the destination region. Moreover, French (Italian) exposed refugees only benefit from French-(Italian-) speaking destinations, but not vice versa. Contrasting the language match with co-ethnic networks, we find that high quality networks are acting as a substitute rather than a complement.
Keywords: F22; I12; J13; J24; J61; J62; 330; Infant health; Language Proffciency; Refugee allocation; Networks